Analisis Kecelakaan Kerja Pada Refurbish Crane Dengan Pendekatan Metode HAZOP - Andivas, Marulan; Wahyu Ismail Kurnia; Mada, Putri Nuvira; Wahono, Novia Febryantri; Wibowo5, Agus Hindarto (Metode : Jurnal Teknik Industri, 2024)
Currently, Indonesia has a fairly high number of accidents. According to BPJS Employment for 2018 - 2022, work accident cases are starting to increase There were (265,334) cases of work accidents recorded in Indonesia in 2022, an increase of around 13.26% from the previous year of (234,270) cases. K3 is a factor that functions to reduce the number of work accidents, as well as supporting the smooth production process, so it must be determined in each agency PT. X is a company engaged in the fields of manufacturing, design, supply, installation, steel fabrication, service, refurbish, remanufacturing equipment and components or parts for mining, gas and oil and other general industries. Work accidents were found in the product support section, such as being pinched and crushed. In this research, we analyze the potential for work accidents using the HAZOP method in the crane refurbishment process which has a risk of work accidents. The attitude of workers at PT. X has 10 activities with potential and risk of danger where there are 3 levels of danger in the extreme category, 5 levels of danger in the high category, 2 levels of danger in the medium category, and 12 levels of danger in the low category.